Oxytocin as an Anti-obesity Treatment - Niu, JingJing; Tong, Jenny; Blevins, James E. (Frontiers in Neuroscience, 2021)
Obesity is a growing health concern, as it increases risk for heart disease, hypertension, type 2 diabetes, cancer, COVID-19 related hospitalizations and mortality. However, current weight loss therapies are often associated with psychiatric or cardiovascular side effects or poor tolerability that limit their long-term use. The hypothalamic neuropeptide, oxytocin, mediates a wide range of physiologic actions, which include reproductive behavior, formation of prosocial behaviors and control of body weight. We and others have shown that OT circumvents leptin resistance and elicits weight loss in diet-induced obese rodents and nonhuman primates by reducing both food intake and increasing energy expenditure (EE). Chronic intranasal OT also elicits promising effects on weight loss in obese humans. This review evaluates the potential use of OT as a therapeutic strategy to treat obesity in rodents, nonhuman primates, and humans, and identifies potential mechanisms that mediate this effect. This review assesses the potential use of OT as a therapeutic strategy for treatment of obesity in rodents, nonhuman primates, and humans, and identifies potential mechanisms that mediate this effect.